The Role of The Government in Development of Community-Based Tourism on Economic Growth Inclusivity - Triana Lidona Aprilani; Yuliarmi Yuliarmi; AAIN Marhaeni (AIBPM Publisher, 2021)
Tourism sectors have great potentials in increasing regional income. The program from the government to increase the number of tourisms is to prioritize tourism development, one of which is tourism on Lombok Island. The purpose of this study is to evaluate the government role in the development of community-based tourism in Lombok, especially the Mandalika Special Economic Zone in Central Lombok Regency. The analysis technique used in this study is to use convinience sampling techniques that are rarely used in previous tourism research in Lombok. The study contended that government role in the development of community-based tourism includes planning, development of main facilities, tourism expenditure policies, making and enforcing regulations. It also underlined that the driving factors in economic growth required participation of local communities. The inhibiting factors of local communities are educational background, employment, and gender.